2014
DOI: 10.1016/j.virol.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of peripheral CD8+T cell responses to SIVΔnef and SIVmac251 challenge reveals a link between protective immunity and induction of systemic immunoregulatory mechanisms

Abstract: Immunization of macaques with attenuated simian immunodeficiency virus (SIV) with deletions in nef (SIVΔnef) is shown to elicit protective immunity to infection by pathogenic SIV, yet the mechanisms that orchestrate protection and prevent pathogenesis remains unknown. We utilized whole-genome transcriptional profiling to reveal molecular signatures of protective immunity in circulating CD8+ T cells of rhesus macaques vaccinated with SIVmac239Δnef and challenged with pathogenic SIVmac251. Our findings suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…A critical future question will be to determine whether immune responses that are effective in controlling ⌬GY will enable pig-tailed macaques to resist pathogenic challenge viruses. Although the SIV ⌬Nef model, in which SIVmac239 is attenuated by deletion of its nef gene, remains the best model for protection from homologous SIV challenges (116)(117)(118), ⌬Nef provides less effective protection from heterologous SIV or simian-human immunodeficiency virus (SHIV) challenges (119)(120)(121). Studies in pig-tailed macaques that assess the ability of ⌬GY infection to elicit protective immune responses are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…A critical future question will be to determine whether immune responses that are effective in controlling ⌬GY will enable pig-tailed macaques to resist pathogenic challenge viruses. Although the SIV ⌬Nef model, in which SIVmac239 is attenuated by deletion of its nef gene, remains the best model for protection from homologous SIV challenges (116)(117)(118), ⌬Nef provides less effective protection from heterologous SIV or simian-human immunodeficiency virus (SHIV) challenges (119)(120)(121). Studies in pig-tailed macaques that assess the ability of ⌬GY infection to elicit protective immune responses are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the induction of IFN signaling pathways in CD8 + T cell transcriptional responses of vaccinated and unvaccinated animals has been demonstrated and vaccine‐based protective immunity to HIV/SIV infection in CD8 + T cells is associated with differential regulation of interferon signaling pathways . George et al.…”
Section: Discussionmentioning
confidence: 99%
“…George et al. , reported that although significant changes in transcription of IFNα were not detected during the vaccination period or following challenge of the vaccinated animals, numerous IFN‐induced factors were up regulated in circulating CD8 + T cells of unvaccinated animals at 3 weeks post infection including IFITM3, IFI6, IFI27, IFI35, and IFI44. Similar induction of IFN associated genes was comparatively absent at all time points during the vaccination period and again at 3 weeks post challenge in SIV Δnef vaccinated animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations